Implementation of Multicultural Education Values in Higher Education: A Case Study of Indonesian Universities - Rohartati, Sri; Maftuh, Bunyamin; Sopandi, Wahyu; Subekti, Eri; Zuhro, Putri Fatimatuz (Indonesia Approach Education, 2024)
The purpose of this research is to describe the implementation of multicultural education ideals at Langlangbuana University, as well as the significance of multicultural education for students and lecturers at the university. As a research subject, Langlangbuana University may have been chosen because of its diversity or special initiatives in implementing multicultural education. This research can identify how these values are implemented in the curriculum, extracurricular activities, and university life in general. A qualitative case study methodology is used in this work. This research is organized and structured in such a way that it is based on facts that occur in the field to gain answers to the research questions. Each participant responds to questions about the implications and importance of values in intercultural education at Langlangbuana University by drawing on their knowledge of specific cases or experiences. Tolerance values, democratic values, justice values, and patriotic values are among the multicultural education values implemented at Langlangbuana University. In-depth observations and interviews were used to describe the attitudes of Langlangbuana University students and lecturers toward tolerance, democracy, justice, and patriotism. Despite their differing religions, they get along well and appreciate each other. The relevance of multicultural education at Langlangbuana University can help students and lecturers comprehend and be conscious of Indonesia's diversity, as well as create mutual respect and collaboration among students and lecturers. Aside from that, multicultural education can assist students and lecturers in creating a pleasant learning atmosphere with mutual respect between individuals from various backgrounds. This research could be one of the few or even the research that in-depth examines the implementation of multicultural education at Langlangbuana University.